2011
DOI: 10.3168/jds.2010-3761
|View full text |Cite
|
Sign up to set email alerts
|

Survey of dairy housing and manure management practices in California

Abstract: In 2007, a descriptive survey was mailed to all dairies in Glenn (G) and Tulare (T) Counties to identify current and future opportunities of manure management practices on California dairies. The purpose was to provide baseline information for development of outreach curriculum and a decision support tool to quantify potential benefits of various N management options on dairy farms. Such baseline information is valuable to staff regulating dairy facilities (e.g., San Joaquin Valley Unified Air Pollution Contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 2 publications
(1 reference statement)
0
25
0
Order By: Relevance
“…In Pennsylvania, farms collecting solid manure mainly did so via bedded pack, while 84% of farms collecting slurry, semisolid or liquid manure employed scrape collection techniques (Dou et al 2001). However, in California, larger farms also used manure as bedding, but did so following collection of corral scrapings and/or processing to separate out solids and liquids (Meyer et al 2011). This contradiction exemplifies a theme in the literature; namely, that there can be substantial variability in manure collection methods across farm size and regions (Powell et al 2005, Sheppard et al 2011.…”
Section: Manure Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Pennsylvania, farms collecting solid manure mainly did so via bedded pack, while 84% of farms collecting slurry, semisolid or liquid manure employed scrape collection techniques (Dou et al 2001). However, in California, larger farms also used manure as bedding, but did so following collection of corral scrapings and/or processing to separate out solids and liquids (Meyer et al 2011). This contradiction exemplifies a theme in the literature; namely, that there can be substantial variability in manure collection methods across farm size and regions (Powell et al 2005, Sheppard et al 2011.…”
Section: Manure Collectionmentioning
confidence: 99%
“…Aside from digester technology, another manure processing technique discussed widely in the literature is solid-liquid separation. Meyer et al concluded that dairy farms in California's Central Valley increased the use of solid-liquid separation from 54% in 1994 to up to 70% in 2007 (Meyer et al 2011). However, in Wisconsin, less than 17% of farms utilized manure separation technology, via either solid-liquid separation or sand separation (Aguirre-Villegas and Larson 2017).…”
Section: Manure Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…From a practical point of view, manure collection is strictly related to housing systems and bedding options. Conveyance cleaning systems like scraping, flushing-scraping and flushing are common in free stall sheds with solid floors, while in sheds with slatted floors manure is removed by gravity, and litter is manually renewed if present in resting areas (Meyer et al, 2011). Scrapers mechanically collect excreta preserving their characteristics, while flushing systems collects excreta hydraulically, diluting them.…”
Section: Introductionmentioning
confidence: 99%
“…[3]. Exposure of butter and butter fat to high temperatures, light and air did not cause a marked change in the iodine numbers and this exposure did not cause rancidity [4].…”
Section: Introductionmentioning
confidence: 99%